Existence of multiple positive solutions for quasilinear elliptic systems involving critical hardy–sobolev exponents and sign-changing weight function - Nyamoradi, Nemat (Mathematical Modelling and Analysis, 2012)
In this paper, we consider a class of quasilinear elliptic systems with weights and the nonlinearity involving the critical Hardy–Sobolev exponent and one sign-changing function. The existence and multiplicity results of positive solutions are obtained by variational methods.